Use of the ITS primers, ITS1F and ITS4, to characterize fungal abundance and diversity in mixed-template samples by qPCR and length heterogeneity analysis - Manter, D.K.; Vivanco, J.M.
Molecular-based approaches to assess microbial biomass and diversity from soil and other ecosystems are rapidly becoming the standard methodology for analysis. While these techniques are advantageous, because they do not rely on the need to culture organisms, each technique may have its own biases and/or limitations when used to assess fungal diversity from mixed-template samples. In this study, we analyzed PCR specificity and efficiency of the ITS primers (ITS1F and ITS4)in a series of single- and mixed-template samples using a combined quantitative PCR-length heterogeneity analysis (LH-qPCR)approach. As expected, these primers successfully amplified all higher fungal species tested (10 ascomycetes, 6 basidiomycetes, and 4 zygomycetes)and no members of the oomycetes. Based on our results, and a search of the GenBank database, amplicons of the ITS1F and ITS4 primer set exhibit considerable variability (420 to 825 bp), but due to similarities in amplicon sizes of some fungal species, actual species diversity in environmental samples may be underestimated approximately two-fold. The addition of an initial qPCR step allowed for the accurate quantitation of total fungal DNA in mixed-template samples over five orders of magnitude (10. 1 to 103 pg ìl. 1). PCR biases between individuals in mixed-templates rendered it impossible to determine the absolute quantity of any individual within a population from its individual peak height. However, relative changes in individuals within a mixed-template sample could be determined due to a constant proportionality between peak heights and starting template concentration. Variability associated with the individual steps of the LH-qPCR analysis was also determined from environmental samples.
Keywords: MOLECULAR ECOLOGY; FUNGI; DIVERSITY; SOIL; DNA